An analysis of leadership characteristics of search and rescue volunteers - Burak Gurer; İlhan Adılogulları (Türk Spor ve Egzersiz Dergisi)
The main purpose of this study was to analyze the leadership behaviors of volunteer leaders in search and rescue field. 118 volunteer leaders attended this study on a volunteer basis. Data were collected through the use of the Multifactor Leadership Questionnaire, which was developed by Bass amp; Avolio (1985) and adapted into Turkish by Demir amp; Okan. 20 items were used to measure transformational leadership while 16 of them were applied for transactional leadership. One Way Anova and T-test statistics were used in order to evaluate the data. Consequently, it was observed that intellectual motivation and individualized consideration of the participants change according to educational variables. Management-by-exception in its passive form indicated a remarkable difference in terms of gender. It is also found that leaders are expected to motivate the members mentally in order to increase the level of motivation. High level of the individual knowledge of a leader is pointed out as an important issue by the participants. Although there is an autocratic structure in search and rescue, a good leader-member relationship is thought to provide certain advantages. Accordingly, the leader who could promote trust among the members of the team is perceived as a sophisticated leader.